2021
DOI: 10.1021/acsami.1c14818
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Resveratrol-Selenium-Peptide Nanocomposites Alleviates Alzheimer’s Disease-like Pathogenesis by Inhibiting Aβ Aggregation and Regulating Gut Microbiota

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease associated with amyloid-β (Aβ) deposition, leading to neurotoxicity (oxidative stress and neuroinflammation) and gut microbiota imbalance. Resveratrol (Res) has neuroprotective properties, but its bioavailability in vivo is very low. Herein, we developed a small Resselenium-peptide nanocomposite to enable the application of Res for eliminating Aβ aggregate-induced neurotoxicity and mitigating gut microbiota disorder in aluminum chloride (AlCl 3 ) and D-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…The Morris Water Maze (MWM) experiment was performed as described previously. 18 The experiment lasted for 7 days that consisted of five training days. During training day, mice were swim freely to find the escape platform in 90 s. At the last day, the escape platform was removed, and the number of each time that the mice passed through the platform area in memory and the escape latency was recorded to evaluate their spatial memory.…”
Section: Stability Of Senps With Different Surface Modificationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Morris Water Maze (MWM) experiment was performed as described previously. 18 The experiment lasted for 7 days that consisted of five training days. During training day, mice were swim freely to find the escape platform in 90 s. At the last day, the escape platform was removed, and the number of each time that the mice passed through the platform area in memory and the escape latency was recorded to evaluate their spatial memory.…”
Section: Stability Of Senps With Different Surface Modificationsmentioning
confidence: 99%
“…Aβ deposition and microglia were analyzed by immunofluorescence staining as described previously. 18 2.6. Analysis of Gut Microbiota Composition.…”
Section: Stability Of Senps With Different Surface Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies suggest that despite the low bioavailability, resveratrol treatment is effective, safe, and well-tolerated in elderly individuals with age-related diseases and may promote healthy aging ( Movahed et al, 2020 ; Harper et al, 2021 ). Moreover, resveratrol and its metabolites can permeate the blood-brain barrier ( Turner et al, 2015 ), offering some supportive grounds for animal studies that have suggested resveratrol and its enhanced nano-formulations as potential anti-Alzheimer’s disease drugs ( Li et al, 2021b ). Aside from neurodegenerative diseases, resveratrol is beneficial for various diabetes-related organ injuries, including diabetic neuropathy, diabetic retinopathy, diabetes-induced liver damage, and cardiovascular diseases.…”
Section: Clinical Utility and Control Of Biological Aging And Age-rel...mentioning
confidence: 99%